2020
DOI: 10.3390/md18090478
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening of Marine Natural Compounds by Means of Chemoinformatics and CDFT-Based Computational Peptidology

Abstract: This work presents the results of a computational study of the chemical reactivity and bioactivity properties of the members of the theopapuamides A-D family of marine peptides by making use of our proposed methodology named Computational Peptidology (CP) that has been successfully considered in previous studies of this kind of molecular system. CP allows for the determination of the global and local descriptors that come from Conceptual Density Functional Theory (CDFT) that can give an idea about the chemical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…However, this is not always possible due to the lack of experimental results for the molecular systems that are being studied or the large size of the molecules that keep some accurate methodologies computationally practical. For this reason, we have developed a protocol named Koopmans in DFT (KID) [ 92 , 93 , 94 ], which is an attempt to validate a given density functional in terms of its internal coherence. Within the KID protocol, four descriptors have been defined where it has been shown that there is a connection between those descriptors and the simplest conformity to the theorem of Koopmans or the Ionization Energy theorem, which is its equivalent within the Generalized Kohn–Sham (GKS) version of DFT, by connecting the electronic energy of the Highest Occupied Molecular Orbital (HOMO)—that is, —with the negative if the ionization energy, I, and the electronic energy of the Lowest Unoccupied Molecular Orbital (LUMO)—that is —with the negative of the Electron affinity, A, giving rise to , , and , where , and represents the ground state energy of the neutral molecule, of the radical cation and the radical anion, respectively, in the geometry of the neutral molecule.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is not always possible due to the lack of experimental results for the molecular systems that are being studied or the large size of the molecules that keep some accurate methodologies computationally practical. For this reason, we have developed a protocol named Koopmans in DFT (KID) [ 92 , 93 , 94 ], which is an attempt to validate a given density functional in terms of its internal coherence. Within the KID protocol, four descriptors have been defined where it has been shown that there is a connection between those descriptors and the simplest conformity to the theorem of Koopmans or the Ionization Energy theorem, which is its equivalent within the Generalized Kohn–Sham (GKS) version of DFT, by connecting the electronic energy of the Highest Occupied Molecular Orbital (HOMO)—that is, —with the negative if the ionization energy, I, and the electronic energy of the Lowest Unoccupied Molecular Orbital (LUMO)—that is —with the negative of the Electron affinity, A, giving rise to , , and , where , and represents the ground state energy of the neutral molecule, of the radical cation and the radical anion, respectively, in the geometry of the neutral molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Within the KID protocol, four descriptors have been defined where it has been shown that there is a connection between those descriptors and the simplest conformity to the theorem of Koopmans or the Ionization Energy theorem, which is its equivalent within the Generalized Kohn–Sham (GKS) version of DFT, by connecting the electronic energy of the Highest Occupied Molecular Orbital (HOMO)—that is, —with the negative if the ionization energy, I, and the electronic energy of the Lowest Unoccupied Molecular Orbital (LUMO)—that is —with the negative of the Electron affinity, A, giving rise to , , and , where , and represents the ground state energy of the neutral molecule, of the radical cation and the radical anion, respectively, in the geometry of the neutral molecule. An additional descriptor, ∆SL, was designed [ 92 , 93 , 94 ] to help in the verification of the accuracy of the KID approximation by comparing the HOMO energy of the radical anion with the energy of the LUMO of the neutral species. Although the Koopmans complaint behavior of the MN12SX density functional has been proven previously for the case of peptides [ 92 , 93 , 94 ], we think that it is worth performing a further validation for the case of the molecules considered in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Range-separated (RS) exchange-correlation density functionals are of extraordinary concern in Kohn-Sham DFT calculations (Iikura et al, 2001;Yanai et al, 2004;Heyd and Scuseria, 2004;Chai and Head-Gordon, 2008;Stein et al, 2009a;Stein et al, 2009b;Stein et al, 2010;Karolewski et al, 2011;Kuritz et al, 2011;Ansbacher et al, 2012;Kronik et al, 2012;Stein et al, 2012). A methodology called KID (Koopmans in DFT) has been established by our research group (Frau et al, 2018;Flores-Holguín et al, 2019a;Frau et al, 2019;Flores-Holguín et al, 2019c;Flores-Holguín et al, 2020;Flores-Holguín et al, 2020a;Flores-Holguín et al, 2020b;Flores-Holguín et al, 2021), t for the validation of a given density functional in terms of its internal coherence. Several descriptors associated with the results of the HOMO and LUMO calculations are related to the results obtained from the estimation of the vertical I and A following the ΔSCF procedure, where SCF refers to the Self-Consistent Field technique.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…The study is complemented by considering the report of some additional properties of potential application in Structure Activity Relationships (SAR) research for the development of therapeutic drugs, and also with the bioactivity radars related to the drug-like behavior of the studied peptides, their predicted biochemical targets and the values associated with Pharmacokinetics and ADMET properties (Daina et al, 2017;Pires et al, 2015;Daina et al, 2019) through standard Chemoinformatics procedures (Begam and Kumar, 2012;González-Medina et al, 2017). By considering this integrative strategy, called Conceptual DFT-based Computational Peptidology as a branch of Computational Chemistry dedicated to the study of peptides and cyclopeptides, the current research represents an extension of our recent studies on the properties of some families of therapeutic peptides of marine origin (Frau et al, 2018;Flores-Holguín et al, 2019a;Frau et al, 2019;Flores-Holguín et al, 2019c;Flores-Holguín et al, 2020;Flores-Holguín et al 2020a;Flores-Holguín et al, 2020b;Flores-Holguín et al, 2021).…”
Section: Introductionmentioning
confidence: 99%